Islamic Corporate Governance and Intellectual Capital: Drivers or Detractors of Sustainability Disclosure? - Nastiti, Ari Sita; Nuha, Gardina Aulin (Faculty of Islamic Economics and Business, Universitas Islam Negeri Ar-Raniry, 2025)
This study investigates the relationship between Islamic Corporate Governance (ICG), intellectual capital, and the disclosure of sustainability reports among companies listed on the Indonesia Sharia Stock Index (ISSI). As sustainability reporting becomes increasingly important in promoting transparency and ethical accountability, especially within Islamic economic systems, this research aims to evaluate whether Sharia-based governance and intangible assets influence sustainability disclosure practices. Using a purposive sampling method, data were collected from 69 companies listed on the Jakarta Islamic Index 70 (JII70) as of November 2022. Sustainability reporting was measured using a checklist adapted from the Global Reporting Initiative (GRI), while ICG and intellectual capital were assessed using modified instruments based on Haniffa and Cooke (2005) and the VAIC™ model by Pulic (2000), respectively. The findings reveal that ICG does not significantly affect sustainability report disclosure, while intellectual capital exhibits a significant negative effect. Among control variables, only company size shows a significant positive relationship with sustainability disclosure. These results suggest that the implementation of ICG in Indonesia remains limited and that firms with high intellectual capital may prioritize internal development over transparency. The study contributes to the literature on Islamic business ethics and highlights the need for stronger integration of Sharia values and governance structures in sustainability practices.========================================================================================================ABSTRAK - Islamic Corporate Governance dan Modal Intelektual: Pendorong atau Penghambat Pengungkapan Keberlanjutan? Penelitian ini mengkaji hubungan antara Islamic Corporate Governance (ICG), modal intelektual, dan pengungkapan laporan keberlanjutan pada perusahaan yang terdaftar dalam Indeks Saham Syariah Indonesia (ISSI). Seiring meningkatnya pentingnya pelaporan keberlanjutan dalam mendorong transparansi dan akuntabilitas etis, khususnya dalam sistem ekonomi Islam, penelitian ini bertujuan untuk mengevaluasi apakah tata kelola berbasis syariah dan aset tidak berwujud memengaruhi praktik pengungkapan keberlanjutan. Dengan menggunakan metode purposive sampling, data dikumpulkan dari 69 perusahaan yang masuk dalam Jakarta Islamic Index 70 (JII70) per November 2022. Pelaporan keberlanjutan diukur menggunakan daftar periksa yang diadaptasi dari Global Reporting Initiative (GRI), sementara ICG dan modal intelektual diukur menggunakan instrumen modifikasi dari Haniffa dan Cooke (2005) serta model VAIC™ dari Pulic (2000). Hasil penelitian menunjukkan bahwa ICG tidak berpengaruh signifikan terhadap pengungkapan laporan keberlanjutan, sedangkan modal intelektual berpengaruh negatif secara signifikan. Di antara variabel kontrol, hanya ukuran perusahaan yang berpengaruh positif secara signifikan terhadap pengungkapan keberlanjutan. Temuan ini mengindikasikan bahwa implementasi ICG di Indonesia masih terbatas dan perusahaan dengan modal intelektual tinggi cenderung lebih fokus pada pengembangan internal daripada transparansi. Studi ini memberikan kontribusi terhadap literatur etika bisnis Islam dan menekankan perlunya integrasi yang lebih kuat antara nilai-nilai syariah dan struktur tata kelola dalam praktik keberlanjutan.